Estrategias para el fortalecimiento de la cultura organizacional de la Agencia Nacional de Hidrocarburos (2021)
This research aims at characterizing the organizational culture of the National Hydrocarbons Agency through the methodology proposed by Cameron and Quinn (1999), which is based on the values by competence model. Using a mixed approach, data from different dimensions of the organizational culture were collected through the Organizational Cultural Assessment Instrument (OCAI) questionnaire, designed, and statistically validated by these authors. The study population was made up of a total of 220 collaborators from all National Hydrocarbons Agency instances. From the data obtained, the current culture, the desired culture and the required culture were determined based on four classes of generic cultures: clan/collaboration, hierarchical/control, adhocracy/creation, and market/competitiveness. The differences and similarities detected between the types of culture stressed the gaps between the required and the desired culture.